The Outcomes and Success Rates of Kasai Operation for Biliary Atresia Cases Using Presurgical Hepatobiliary Scan: Observations at NINMAS - Islam, Urnus; Reza, Sharmin; Adnan, Sheikh Md; Chowdhury, Md Shafiqul Alam; Bailey, Shamsun Nahar; Perveen, Rahima; Ananna, Farzana Rahman; Sultana, Nasreen (Bangladesh Journal of Nuclear Medicine, 2024)
Abstract not avaiable Bangladesh J. Nuclear Med. 27(1): 44-48, 2024